Detection of immunoglobulin G antibodies to Neospora caninum in humans: High seropositivity rates in patients who are infected by human immunodeficiency virus or have neurological disorders - Lobato, J.; Silva, DAO; Mineo, TWP; Amaral, JDHF; Segundo, GRS; Costa-Cruz, J. M.; Ferreira, M. S.; Borges, A. S.; Mineo, JR (Amer Soc Microbiology, 2006)
Considering that little is known about the epidemiology of Neospora caninum infection in humans, particularly in populations with high Toxoplasma gondii infection rates, the present study aimed to investigate the presence of antibodies to N. caninum in T. gondii-seropositive and -seronegative individuals. A total of 256 serum samples divided into four groups (61 samples from human immunodeficiency virus [HIV]-positive patients, 50 samples from patients with neurological disorders, 91 samples from newborns, and 54 samples from healthy subjects) were assessed for N. caninum and T. gondii serologies by indirect fluorescent-antibody test, enzyme-linked immunosorbent assay, and immunoblotting (IB). Immunoglobulin G antibodies to N. caninum were predominantly detected in HIV-infected patients (38%) and patients with neurological disorders (18%), while newborns and healthy subjects showed lower seropositivity rates (5% and 6%, respectively). Seropositivity to N. caninum was significantly associated with seropositivity to T. gondii in both HIV-infected patients and patients with neurological disorders. Seroreactivity to N. caninum was confirmed by IB, with positive sera predominantly recognizing the 29-kDa antigen of N. caninum. The results of this study indicate the presence of N. caninum infection or exposure in humans, particularly in HIV-infected patients or patients with neurological disorders, who could have opportunistic and concurrent infections with T. gondii. These findings may bring a new concern for the unstable clinical health of HIV-infected patients and the actual role of N. caninum infection in immunocompromised patients.